Embedding Professional Skills in the ICT Curriculum - Von Konsky, Brian; Jones, A.; Miller, C. (Macquarie University, Sydney, 2013)
This paper reports on a preliminary investigation into the technology and techniques for designing and managing higher education programs in Information and Communications Technology (ICT). The approach outlined is based on the Skills Framework for the Information Age (SFIA) and is informed by data arising from the Australian Computer Society (ACS) Computer Professional education Program (CPeP). It is intended that this work will inform subsequent research to improve dialogue between Industry Advisory Boards, Professional Societies, and their academic partners as they design, implement, and accredit higher education programs in ICT. It is further intended that this will contribute to the development of ICT curriculum that is aligned with industry expectations and prepares ICT graduates for professional practice. Future directions for improving SFIA based curriculum design and facilitating better stakeholder communication and collaboration are discussed.